Recent developments in flame-retardant lignin-based biocomposite: manufacturing, and characterization - Solihat, Nissa Nurfajrin; Hidayat, Alif Faturahman; Mohammad Taib, Mohamad Nurul Azman; Hussin, M. Hazwan; Lee, Seng Hua; Abd Ghani, Muhammad Aizat; Al Edrus, Syeed Saifulazry Osman; Vahabi, Henri; Fatriasari, Widya (Springer, 2022)
Lignin with a phenolic structure can act as a fire retardant, but different origins of lignin and extraction methods impact the fire behavior capabilities. The thermal characteristics of lignin, such as glass transition (Tg) temperature, thermal degradation, molecular weight, lignin purity, and phenolic content, influence the capability of lignin as a flame retardant (FR) by causing significant char residue. However, lignin faced significant constraints in the final polymer to meet industry requirements, with the main issue being a lack of homogeneity when blending lignin with polymeric matrices. To improve the FR performance of lignin, various advances have been taken such as altering lignin with nitrogen and/or phosphorus chemicals, as well as shrinking lignin to the nanoscale to reduce lignin aggregation with matrices and obtaining considerable FR behavior in which FR system, lignin can present as a single component, lignin-based composite, modified lignin, and nano lignin. The present review addresses the manufacture of lignin as FR and the attributes of the product with lignin added to the system. It also covers the structure, source, extraction technique, physical-chemical properties, and chemical modification of lignin as an FR source, as well as the basic principle of flame retardancy, influencing factors (current development and application till the industrial analysis need of FR). Throughout this review, it aids in the discovery of a better strategy to introduce lignin as a source of bio-based FR for achieving the low cost in the fabrication method of FR.